2014
DOI: 10.1089/vbz.2014.1648
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epizootiology and Diagnosis of Porcine Babesiosis in Sardinia, Italy

Abstract: The recent characterization of the 18S ribosomal RNA (rRNA) of a pathogenic Babesia species in a domestic sow paved the way for establishing diagnostic and epidemiological tools for porcine babesiosis. Here, we developed the first specific Babesia sp. Suis PCR, and we applied this test to a panel of samples collected from animals living in a typical Mediterranean environment (Sardinia, Italy), including domestic pigs, wild boars, and ticks. In domestic pigs, PCR coupled with sequencing revealed an estimated Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Babesia sp. Anglona was previously identified in symptomatic and asymptomatic domestic pigs as well as in Rhipicephalus ticks in Sardinia [27]. In the present study, DNA of T. ovis was also identified in Rhipicephalus ticks.…”
supporting
confidence: 75%
“…Babesia sp. Anglona was previously identified in symptomatic and asymptomatic domestic pigs as well as in Rhipicephalus ticks in Sardinia [27]. In the present study, DNA of T. ovis was also identified in Rhipicephalus ticks.…”
supporting
confidence: 75%
“…Variation in disease severity and clinical manifestations may be due to pathogen factors or the response of the host to infection. Zobba et al speculated that different strains identified in clinically ill and in asymptomatic pigs may be responsible for different degrees of pathogenicity (12).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences were compared to the GenBank database for homologous sequences using nucleotide blast BLASTN (18). Phylogenetic analyses were performed by aligning the partial 18S rRNA sequences obtained from this case with a set of 20 sequences ( Supplementary Table 2), mainly representative of the Babesidae clade VI, as previously described (6,12,19). The Ungulibabesids, as previously defined by Criado-Fornelio et al (16) fall within this clade of Babesiadae and is where Babesia sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation